A New Regulatory Paradigm for the Digital Sector in Europe - Georg Serentschy (Intereconomics, 2018)
The new regulatory framework in the digital sector in Europe is likely to fall short of expectations. A fragmented digital market with insuffi cient incentives for investment is the probable outcome. European regulators should abandon their approach in favour of a new and more flexible set of ideas discussed in this paper.
Keywords: 330; Digital Single Market; Investment policy; Market regulation; Regulatory policies